Gαi1 and Gαi3mediate VEGF-induced VEGFR2 endocytosis, signaling and angiogenesis - Sun, Jian (Theranostics, 2018)
VEGF binding to VEGFR2 leads to VEGFR2 endocytosis and downstream signaling activation to promote angiogenesis. Methods: Using genetic strategies, we tested the requirement of α subunits of heterotrimeric G proteins (Gαi1/3) in the process. Results: Gαi1/3 are located in the VEGFR2 endocytosis complex (VEGFR2-Ephrin-B2-Dab2-PAR-3), where they are required for VEGFR2 endocytosis and downstream signaling transduction. Gαi1/3 knockdown, knockout or dominant negative mutation inhibited VEGF-induced VEGFR2 endocytosis, and downstream Akt-mTOR and Erk-MAPK activation. Functional studies show that Gαi1/3 shRNA inhibited VEGF-induced proliferation, invasion, migration and vessel-like tube formation of HUVECs. In vivo, Gαi1/3 shRNA lentivirus inhibited alkali burn-induced neovascularization in mouse cornea. Further, oxygen-induced retinopathy (OIR)-induced retinal neovascularization was inhibited by intravitreal injection of Gαi1/3 shRNA lentivirus. Moreover, in vivo angiogenesis by alkali burn and OIR was significantly attenuated in Gαi1/3 double knockout mice. Significantly, Gαi1/3 proteins are upregulated in proliferative retinal tissues of proliferative diabetic retinopathy (PDR) patients. Conclusion: These results provide mechanistic insights into the critical role played by Gαi1/3 proteins in VEGF-induced VEGFR2 endocytosis, signaling and angiogenesis.